A Grammar of Akajeru Fragments of a traditional North Andamanese dialect - Zamponi, Raoul (Grammars of World and Minority Languages, 2021)
A Grammar of Akajeru describes aspects of the grammatical system and lexicon of Akajeru, a traditional dialect of the North Andamanese language, as it was reportedly used around the beginning of the twentieth century. It is based primarily on the fragments of this variety provided by the British anthropologist Alfred R. Radcliffe-Brown and scattered among the published results of his anthropological research carried out on the islands between 1906 and 1908. These are supplemented by published lists of 46 anatomical terms and 28 toponyms collected by Edward Horace Man, Officer in Charge of the Andamanese 1875-79. The book provides a linguistic analysis of all the extant Akajeru material, plus items identified by Radcliffe-Brown as 'North Andaman' without further specification, his few records of Akabo and Akakhora and Man's few records of Akakhora, which together constitute all the documentation of these other traditional North Andamanese dialects. It includes a grammatical sketch of Akajeru, a list of all the words that were recorded, together with an English-Akajeru finder list, and a comparison between Akajeru and Present-day Andamanese, an Akajeru-based variety with elements from all the other traditional dialects of North Andamanese that is today remembered by only three people.